The impact of blastocyst grade on singleton birth weight in fresh IVF‒ET cycles in ART: a retrospective study - Senlin Shi; Boya Zhao; Zhan Hu; Qiongyao Shi (BMC, 2024)
Abstract Background The positive correlation between embryo quality and pregnancy outcomes has been confirmed in many studies, but there are few on the impact of embryo quality on neonatal weight, especially among neonates from fresh IVF‒ET cycles in ART. Therefore, this study aimed to compare the birth weights of infants from different blastocyst grades in fresh IVF-ET cycles and explore related factors affecting birth weight. Methods The main outcome measure was singleton birth weight. A total of 1301 fresh cycles of single blastocyst transplantation and single live birth profiles were retrospectively analyzed and divided into four groups according to blastocyst quality: the excellent group (grade AA), which included 170 cycles; the good group (grade AB/BA), which included 312 cycles; the average group (grade BB/CA/AC), which included 559 cycles; and the poor group (grade BC/CB), which included 260 cycles. The relationships among cystic cavity expansion, endocytic cell mass, ectodermal trophoblast cell grade, and birth weight were studied. Multiple linear regression analysis was performed to investigate the relationship between blastocyst quality and neonatal birth weight and logistic regression for the risk factors for low birth weight newborns. Results With decreases in the blastocyst quality, including ICM, TE quality, and embryo expansion stage, birth weight declined, and Z scores correspondingly decreased. After adjusting for confounders, the average and poor groups (P = 0.01 and P = 0.001, respectively) and blastocysts with TE grade C (P = 0.022) resulted in singletons with lower birth weight. Additionally, the poor group and blastocysts with Grade C TEs had a greater chance of leading to low birth weight infants compared with the other groups. Conclusion Our findings indicated that excellent and good-grade blastocyst transplantation could achieve better pregnancy outcomes and that average and poor-grade blastocyst transplantation, especially with grade C TEs, were associated with single birth weight loss. No association was found between the embryo expansion stage or ICM quality and neonatal birth weight.